Testing of potato breeding material for resistance to Globodera rostochiensis (Ro1) - Sigareva, D.; Fedorenko, O.; Taktayev, B. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2018)
The results of laboratory and field estimate of stability of newly created potato breeding material against Globodera rostochiensis (Ro1) are presented. During 2016—2018, 640 breeding samples sent by the leading breeding institutions of the state, namely: the Institute for Potato Research of the NAAS of Ukraine, the Polessky research department the Institute for Potato Research of the NAAS, CJSC NGO “Chernihivelitkartoplya” and the Institute of agriculture of the Carpathian region were tested in laboratory conditions. Among the potato material we studied, most of the samples belonged to the Polessky research department the Institute for Potato Research of the NAAS — 305 (47.7% of the total), where 172 samples (56.4%) of the sent hybrids of the first and second year of the testing were resistance. A higher percent of the resistance of the breeding material was in the potato material of the Institute for Potato Research of the NAAS, which was 68.0% (115 breeding numbers). In laboratory conditions, most of the samples — 57.7% showed resistance to golden potato cyst nematode (GPCN), 16.2% of the samples were weakly resistant and the rest samples — 26.1% of potato hybrids were classified as susceptible. During the field testing, 32 samples were tested, of which 28 were classified as resistance, 2 selective samples were weakly resistant and 2 were susceptible. The majority of resistance selection material on the high-invasive background showed high nematode cleanse ability and good yield, which exceeded control in 1.5—2 times. All resistant forms are a valuable material for introducing into the breeding process for the production of nematode resistant potato varieties, which will keep the crop in the infected areas and will have the ability to clear the soil from golden nematode potatoes.